2016
DOI: 10.1080/1028415x.2016.1144845
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of theanine, caffeine and theanine–caffeine combination on attention

Abstract: A dose of theanine equivalent of eight cups of back tea improves cognitive and neurophysiological measures of selective attention, to a degree that is comparable with that of caffeine. Theanine and caffeine seem to have additive effects on attention in high doses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 37 publications
3
48
1
1
Order By: Relevance
“…Most recently, caffeine (160 mg) and theanine (200 mg) enhanced recognition visual response time and certain event-related potential (ERP) components, specifically N2-P300 amplitudes indicating enhanced attentional processing. Notably, such effects appeared to be additive in that visual response time and N2-P300 amplitudes were similar between caffeine with theanine together and the sum of caffeine and theanine alone (Kahathuduwa et al 2016). Thus, some work suggests that the cognitive benefits of caffeine are similar with and without theanine (Kelly et al 2008;Owen et al 2008), indicating that the cognitive effects of tea may be driven by caffeine, whereas other work suggests that theanine has independent or additive effects when consumed with caffeine (Haskell et al 2008;Kahathuduwa et al 2016).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Most recently, caffeine (160 mg) and theanine (200 mg) enhanced recognition visual response time and certain event-related potential (ERP) components, specifically N2-P300 amplitudes indicating enhanced attentional processing. Notably, such effects appeared to be additive in that visual response time and N2-P300 amplitudes were similar between caffeine with theanine together and the sum of caffeine and theanine alone (Kahathuduwa et al 2016). Thus, some work suggests that the cognitive benefits of caffeine are similar with and without theanine (Kelly et al 2008;Owen et al 2008), indicating that the cognitive effects of tea may be driven by caffeine, whereas other work suggests that theanine has independent or additive effects when consumed with caffeine (Haskell et al 2008;Kahathuduwa et al 2016).…”
Section: Introductionmentioning
confidence: 90%
“…The dose of caffeine chosen was roughly equivalent to an 8-ounce coffee purchased at a local coffee chain (Starbucks short coffee; 180 mg) and the dose of theanine was approximately that which could be consumed with five 8-ounce cups of tea (Cooper et al 2005). Similar doses of theanine have been shown to reduce perceived stress (Kimura et al 2007) and influence attention-related electroencephalographic activity (Gomez-Ramirez et al 2007Kahathuduwa et al 2016). Treatment order was counterbalanced across participants using a complete Latin square.…”
Section: Designmentioning
confidence: 99%
“…As a stimulant, caffeine often increases alertness and improves performance for tasks requiring sustained attention [13]. In addition, it was reported that acute intake of theanine, caffeine, and their significantly improved cognitive and neurophysiological measures of selective attention [14].…”
Section: Introductionmentioning
confidence: 99%
“…All studies considered acute effects of caffeine and had a relatively even distribution of male and female participants. Two studies recruited men only [43,44] and one recruited military personnel [44], with a combined total number of 172 participants. Participants' caffeine consumption was heterogeneous across all included studies, examining low, moderate, high and mixed users.…”
Section: Caffeinementioning
confidence: 99%